Women’s Language Style of Understanding Used in Pitch Perfect Movie. - Eka Putri, A.A. Sg. Istri Adisti; Aryani, I Gusti Agung Istri; Sosiowati, I Gst. Ayu Gede (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
The title of this article is Women’s Language Style of Understanding Used in Pitch Perfect Movie. The article focuses on the language style used by women in movies, specifically understanding, and the function of understanding applied in the movies. This article uses Tannen's theory about women's language style of understanding that was presented by the main characters in Pitch Perfect movies as the data, also the function of understanding that using Holmes’s theory. This study discusses the language style that is used by women in movies, especially understanding, and also the function of understanding applied in the movies. This article used the movie script of Pitch Perfect movie as the main data, and findings showed that women characters often show their understanding towards each other. The data was collected using documentation and note-taking methods from the script and movie website. The study uses the descriptive qualitative method to analyze the types of women’s language styles and their functions. The results are presented in a descriptive way. The result found three (3) findings on women's language style of understanding. The language function used to express understanding were expressive and directive. The women characters in the movie used verbal and nonverbal communication to express their understanding toward each other. This study provides insights into how women use language to express their emotions and the different functions of the language they use to communicate with others. Keywords: Women’s Language Styles, Language Function, Understanding, Movie